2016
DOI: 10.12968/bjon.2016.25.6.s54
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of a haemoglobin spray on size reduction in chronic DFUs

Abstract: The addition of a topical oxygenation therapy in this cohort of non-healing DFUs showed reduction in wound surface area and progression to healing. The product was also found to be acceptable and very easy to use by both participants and clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
(2 reference statements)
0
14
0
Order By: Relevance
“…Hunt et al also found that this was evident as early as the first week of treatment and was observed at all subsequent weeks, up to week 26 22 . Furthermore, all studies of chronic and non‐healing wounds found that such a therapy was effective in promoting wound healing, 15,24,27,31,33 with two studies demonstrating a positive reduction occurring in all patients 24,25 …”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Hunt et al also found that this was evident as early as the first week of treatment and was observed at all subsequent weeks, up to week 26 22 . Furthermore, all studies of chronic and non‐healing wounds found that such a therapy was effective in promoting wound healing, 15,24,27,31,33 with two studies demonstrating a positive reduction occurring in all patients 24,25 …”
Section: Resultsmentioning
confidence: 93%
“…All human research was conducted through the application of a haemoglobin spray (Granulox, SastoMed, Georgsmarienhütte, Germany). It should be noted that number of studies were part of a series, that is, the evaluation of patients at different time points following the intervention 14,15,22,23,25‐28 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations